2020
DOI: 10.1177/1538574420981812
|View full text |Cite
|
Sign up to set email alerts
|

Surgical and Endovascular Management of Isolated Internal Iliac Artery Aneurysms: A Systematic Review and Meta-Analysis

Abstract: Objectives: The purpose of this paper is to report the different modalities for the treatment of isolated internal iliac artery aneurysms (IIIAA), as well as their outcomes. Methods: We performed a systematic review of the literature (database searched: PubMed, Web of Science, Scopus, Cochrane Library; last search: April 2020). We included articles reporting on the outcomes for IIIAA interventions comprising at least 5 patients. Studies were included when presenting extractable outcome data regarding intraoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…According to guidelines, preserving the patency of the internal iliac artery is important whenever possible. 2,3,7 Iliac branch surely represent an option, guaranteeing internal iliac patency, especially for very proximal hypogastric aneurysm or cases where also common or external iliac artery are affected. In contrast, in distal hypogastric aneurysms without common or external iliac arteries affection, iliac branching could be considered an overtreatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to guidelines, preserving the patency of the internal iliac artery is important whenever possible. 2,3,7 Iliac branch surely represent an option, guaranteeing internal iliac patency, especially for very proximal hypogastric aneurysm or cases where also common or external iliac artery are affected. In contrast, in distal hypogastric aneurysms without common or external iliac arteries affection, iliac branching could be considered an overtreatment.…”
Section: Discussionmentioning
confidence: 99%
“…When an internal iliac artery is aneurysmatic, the contralateral one is often diseased too, resulting aneurysmatic in 11.4% cases and occluded in 11.6%. [1][2][3] Nowadays more IIIAAs are occasionally detected still asymptomatic than in the past, thanks to the widespread use of computed tomography angiography (CTA). Despite this, IIIAAs are frequently large and symptomatic at presentation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al reported the largest patient group for isolated IIAA treated by either surgical or endovascular techniques, in which forty-two patients were included (Yang et al 2020 ). A recent systematic review disclosed 202 isolated IIA aneurysms from all publications, reflecting the rarity of this condition (Perini et al 2021 ). Endovascular treatment for isolated IIA aneurysms can be restricted to the IIA if there is sufficient neck length in the proximal IIA to place a vascular plug or coils.…”
Section: Discussionmentioning
confidence: 99%
“…However, the risk of distal sealing-related endoleaks makes the use of iliac branch devices (IBDs) for endovascular aneurysm treatment contraindicated in the presence of a hypogastric aneurysm [6]. Since it provides good shortto mid-term results and low early mortality, endovascular therapy is recommended as the preferable way of treatment in the literature [7]. Manufacturers recommend a proximal aortic endograft implantation in the infrarenal aorta in order to ensure effective proximal sealing of the IBDs.…”
Section: Introductionmentioning
confidence: 99%